2006
DOI: 10.1111/j.1460-9592.2006.01844.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cuffed and uncuffed preformed oral pediatric tracheal tubes

Abstract: There is a need for improvement in cuffed preformed pediatric tracheal tubes, namely a standard bend-to-tracheal tube tip distance to allow a safe insertion depth, a short cuff placed on the tube shaft as distally as possible and an intubation depth mark to verify a proper position of the cuff in the trachea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 25 publications
2
33
0
Order By: Relevance
“…Similar design problems have been encountered with preformed UETT and CETT for children. [31] These tubes may lead to trans-vocal cord cuff placement when the tracheal tube is placed according to the bend because of reduced bend-to-tracheal tube tip distance and the presence of a Murphy eye and longer cuffs.…”
Section: Introductionmentioning
confidence: 99%
“…Similar design problems have been encountered with preformed UETT and CETT for children. [31] These tubes may lead to trans-vocal cord cuff placement when the tracheal tube is placed according to the bend because of reduced bend-to-tracheal tube tip distance and the presence of a Murphy eye and longer cuffs.…”
Section: Introductionmentioning
confidence: 99%
“…It can be due to the fact that our capnography data may not be reliable because we mask ventilated the patients before intubation and there were unequal periods of hypoventilation involved during the placement of NETT. The use of cuffed endotracheal tubes in pediatrics is still controversial [24][25][26]. Many studies show the efficacy of cuffed NETT in terms of lower gas consumption and ease of intubation [24,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Holzki also reported on the inappropriate design of cuffed pediatric tracheal tubes and on overinflated tube cuffs within the pediatric airway being a major source of cuff related airway injury [16]. Similarly, other authors have reported several shortcomings in the design of cuffed pediatric tracheal tubes [17][18][19][20][21][22].…”
Section: Cuffed Tracheal Tubes In Children: Pastmentioning
confidence: 97%
“…This can lead to serious problems with tracheal tube size selection, repeated reintubations and to airway damage [20].…”
Section: Outer Diameter Of Tracheal Tubesmentioning
confidence: 99%